Terahertz Amplitude Polynomial Principle Component Regression for Aramid–Basalt Hybrid Composite Laminate Inspection - Zhang Hai; Sfarra S. Stefano; Osman A. Ahmad; Szielasko K. Klaus; Stumm Ch. Christopher; Sarasini F. Fabrizio; Santulli C. Carlo; Maldague X. Xavier (2018, 2018)
Title screen